A Shelley Chronology - Bradley, J.L. author. aut Link
XII, 93 p.
Keywords: J.L. Bradley's chronology captures much of the drama and excitement of Shelley's life. This is an informative, often witty account which will be extremely valuable to all Shelley students, scholars and enthusiasts. A section on the Shelley circle is a particularly helpful supplement to the main body of the book.